2018
DOI: 10.2320/matertrans.mj201604
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Atomic Size Factors on the Phase Stability of Laves Phase in Nb-Cr-Ni-Al and Nb-V-Ni-Al Phase Diagrams

Abstract: Fig. 1 bcc ss /B2/Laves three-phase elds in quasi-ternary phase diagrams of the (a) Ta-Cr-NiAl, 13) (b) Ta-V-NiAl, 14) (c) Ta-Mo-NiAl, 15) and (d) Nb-Mo-NiAl 16) systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
3
0
2
Order By: Relevance
“…This question of so-called site preference 1 was discussed, for example, in Refs. [16,17,[82][83][84][85][86][87]. Upon adding a third element C to a Laves AB 2 , i.e., moving into the ternary system A-B-C, C may substitute either A or B to form a solid solution of the general formula (A 1-x C x )(B 1-y C y ) 2 , if we, for a moment neglect the possibility of A and B occupying the opposite sublattices.…”
Section: Stability and Site Preferencementioning
confidence: 99%
“…This question of so-called site preference 1 was discussed, for example, in Refs. [16,17,[82][83][84][85][86][87]. Upon adding a third element C to a Laves AB 2 , i.e., moving into the ternary system A-B-C, C may substitute either A or B to form a solid solution of the general formula (A 1-x C x )(B 1-y C y ) 2 , if we, for a moment neglect the possibility of A and B occupying the opposite sublattices.…”
Section: Stability and Site Preferencementioning
confidence: 99%
“…Therefore, it can be concluded that Ti(Co, Cr, Fe, Mn) 2 might be expected to form a Laves phase, and Ti atoms mainly occupy the A-site. It is known that the stability of Laves-type phase is dominated by the atomic size difference between large A-site elements and small B-site elements [30][31][32]. The Laves phase has been confirmed in a wide range 1.05 < r A /r B < 1.68 , although the ideal size difference ratio is r A /r B = 1.225 ,.…”
Section: Phase Stability Of Each Constituent Phasementioning
confidence: 98%
“…Some AB 2 -type intermetallic Laves phases with topologically close-packed (TCP) structures are classified into such an intermetallic compound group. 3,4) There are three major types of Laves phases: the cubic C15 phase, the hexagonal C14 phase and the dihexagonal C36 phase. However, the limitation of these intermetallics is their poor room-temperature toughness.…”
Section: Introductionmentioning
confidence: 99%